2015
DOI: 10.3389/fpls.2015.00479
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of proteome extracted from barley crowns grown under different drought conditions

Abstract: Barley cultivar Amulet was used to study the quantitative proteome changes through different drought conditions utilizing two-dimensional difference gel electrophoresis (2D-DIGE). Plants were cultivated for 10 days under different drought conditions. To obtain control and differentially drought-treated plants, the soil water content was kept at 65, 35, and 30% of soil water capacity (SWC), respectively. Osmotic potential, water saturation deficit, 13C discrimination, and dehydrin accumulation were monitored du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 70 publications
2
37
0
Order By: Relevance
“…The analysis indicated that the differentially regulated proteins were related to photosynthesis, detoxification, energy metabolism and protein biosynthesis. Barley, also, used to identify the quantitative proteome changes under different drought conditions by Vítámvás et al [184]. They cultivated plants for 10 days under different drought conditions that the soil water content was held at 65, 35 and 30% of soil water capacity (SWC), respectively.…”
Section: Genomic Studies On Barleymentioning
confidence: 99%
“…The analysis indicated that the differentially regulated proteins were related to photosynthesis, detoxification, energy metabolism and protein biosynthesis. Barley, also, used to identify the quantitative proteome changes under different drought conditions by Vítámvás et al [184]. They cultivated plants for 10 days under different drought conditions that the soil water content was held at 65, 35 and 30% of soil water capacity (SWC), respectively.…”
Section: Genomic Studies On Barleymentioning
confidence: 99%
“…Furthermore, at the molecular level, drought stress affects gene expression level of different pathways related to stress perception, signal transduction, regulators, and the synthesis of stress-related proteins (Kakumanu et al 2012). Proteomic changes of many plants have been studied under drought stress, including wheat (Faghani et al 2015), barley (Vítámvás et al 2015), cotton (Deeba et al 2012), tobacco (Xie et al 2016), rapeseeds (Urban et al 2016), peanut (Katam et al 2016), grapevine (Król and Weidner 2017), and maize (Benesova et al 2012, Hu et al 2011, Liu et al 2012. Studies of proteins in maize (Kakumanu et al 2012) and wheat (Caruso et al 2009) show that a very close relationship exists between drought resistance and gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the quality of the total protein extracted from the same plant organ using different methods may differ to a certain extent (Saravanan and Rose, 2004;Abdullah et al, 2017). Although research studies have extracted protein from barley, these studies have mainly relied on twodimensional gel electrophoresis (Vítámvás et al, 2015;Guo et al, 2016). Moreover, these reported methods are costly and time-consuming (Ghosh et al, 2014;Wu et al, 2014), easy and stable protein extraction methods for western blotting remain unexplored in barley.…”
Section: Introductionmentioning
confidence: 99%